Solvent-assisted programming of flat polymer sheets into reconfigurable and self-healing 3D structures - Yang Yang (Nature Portfolio, 2018)
It is desirable to programme 2D plastic films into 3D structures without any assisting equipment. Here the authors show this programming can be achieved with a pipette, a hair dryer, and a bottle of solvent by using a commercial epoxy with a small percentage of a specific catalyst to facilitate bond exchange.